Teach us to pray: the Lord's prayer in the early church and today - González, Justo L. (William B. Eerdmans Publishing Co, 2020)
"A meditation on the importance of the Lord's Prayer for contemporary Christian life, with insights drawn from the wisdom and experience of early Christians"--